Diabetic nephropathy: methods and protocols - Gnudi, Luigi; Long, David A. (Methods in molecular biology, 2020)
Diabetic Nephropathy: An Overview -- Modeling Podocyte Biology Using Drosophila Nephrocytes -- A Technique for Studying Glomerular Filtration Integrity in the Zebrafish Pronephros -- Modeling Human Diabetic Kidney Disease by Combining Hyperglycemia and Hypertension in a Transgenic Rodent Model -- Isolating and Culturing Mouse Podocyte Cells to Study Diabetic Nephropathy -- Histological Examination of the Diabetic Kidney -- Sample Preparation and Stereological Methods for the Study of Glomerular Ultrastructure Using Electron Microscopy -- Tissue Clearing and Deep Imaging of the Kidney Using Confocal and Two-Photon Microscopy -- Transcutaneous Measurement of Glomerular Filtration Rate in Rodents -- An In Vitro Method to Analyze Glucose Uptake in Podocytes -- Glomerular Endothelial Cells: Assessment of Barrier Properties In Vitro -- Methods to Detect Endoplasmic Reticulum Stress and Apoptosis in Diabetic Nephropathy -- Isolating Urinary Extracellular Vesicles as Biomarkers for Diabetic Disease -- Examining Cell-Cell Interactions in the Kidney Using AFM Single-Cell Force Spectroscopy -- Genetic Strategies to Understand Human Diabetic Nephropathy: Wet-Lab Approaches -- Genetic Strategies to Understand Human Diabetic Nephropathy: In Silico Strategies for Molecular Data - Association Studies -- Assessment of Urinary MicroRNAs by Quantitative Polymerase Chain Reaction in Diabetic Nephropathy Patients -- Metabolomic and Proteomic Techniques for Establishing Biomarkers and Improving Our Understanding of Pathophysiology in Diabetic Nephropathy -- Formation of Mature Nephrons by Implantation of Human Pluripotent Stem Cell-Derived Progenitors into Mice -- Generating Mutant Renal Cell Lines Using CRISPR Technologies